Wastewater treatment and use in agriculture - Pescod, M. B. (Food and Agriculture Organization of the United Nations, 1992)
This book introduction about wastewater characteristics and effluent quality, wastewater quality guidelines for agricultural use, wastewater treatment, aquifer recharge with wastewater....